Elemental Changes in Barley Leaves After Infection by Rhynchosporium secalis¦ - SORKHILALEHLOO, B.; TEWARI, J.P. (Asian Journal of Chemistry, 2010)
The barley-scald pathosystem was investigated to determine the elemental changes in barley leaves. The potential role of calcium, potassium, silicon and sodium as disease related elements were studied. Energy dispersive X-ray microanalysis (XRM) in conjunction with scanning electron microscopy (SEM) was used to determine elemental changes associated with disease resistance. SEM of barley leaf surfaces inoculated with Rhynchosporium secalis showed various shapes of Ca/K-containing crystals associated with plant cells upon infection. Analysis of Ca, Si, K and Na in the superficial layers of plant tissues showed that the levels of these elements changed significantly after inoculation. The extent of changes was dependent on the barley genotype and interactions with scald isolate(s). Calcium and potassium were commonly detected at high levels in the crystals/druses observed in slow-scalding lines, Zavila and UNA 80 similar to those observed in the susceptible cultivar Stander.